Synthesis and applications of nano-TiO2: a review - Noman, Muhammad Tayyab; Ashraf, Muhammad Azeem; Ali, Azam (Environmental science and pollution research international, 2019)
TiO2-based nanomaterials have attracted prodigious attention as a photocatalysts in numerous fields of applications. In this thematic issue, the mechanism behind the photocatalytic activity of nano-TiO2 as well as the critical properties have been reviewed in details. The synthesis routes and the variables that affect the size and crystallinity of nano-TiO2 have also been discussed in detail. Moreover, a newly emerged class of color TiO2, TiO2 in aerogel form, nanotubes form, doped and undoped form, and other forms of TiO2 have been discussed in details. Photocatalytic and photovoltaic applications and the type of nano-TiO2 that is more suitable for these applications have been discussed in this review.
Keywords: molekulární modely; titan; Catalysis; Nanocomposites; povrchové vlastnosti; Titanium; Models, Molecular; nanostruktury; DSSC; Nano-TiO2; Photovoltaic; Chemistry Techniques, Synthetic; techniky syntetické chemie; Photocatalysis; Nanostructures; katalýza; Surface Properties